2016
DOI: 10.4103/2231-0762.195509
|View full text |Cite
|
Sign up to set email alerts
|

Stress and professional burnout among newly graduated dentists

Abstract: Background:Dentists encounter numerous professional stressful situations, beginning from education to day-to-day practice. The resulting stress tends to have a negative impact on their personal as well as professional lives.Objectives:To measure daily burnout, and to investigate the extent of expectations from dental career and the feeling of being unqualified new dental practitioner.Materials and Methods:A close-ended questionnaire, i.e., “the Copenhagen Burnout Inventory,” was utilized for evaluation. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Previous studies on occupational stress and mental health in dentists have identified burnout as a predisposing factor of depression [ 45 , 46 ]. Burnout indicates mental or emotional exhaustion owing to the long-term exposure to stress [ 47 ]. When dentists suffer from burnout, they typically underestimate their accomplishments in a negative and cynical manner in front of their patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on occupational stress and mental health in dentists have identified burnout as a predisposing factor of depression [ 45 , 46 ]. Burnout indicates mental or emotional exhaustion owing to the long-term exposure to stress [ 47 ]. When dentists suffer from burnout, they typically underestimate their accomplishments in a negative and cynical manner in front of their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Dentists are exposed to a high risk of anxiety and depression since their training as dental college students [ 16 , 25 , 47 , 52 ]. They are also exposed to a high level of stress related to the number of patients per day and workload, general financial status, desire for patient’s excessive requirements, technological perfection needs, and fear of litigation and making mistakes [ 2 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fact of being enrolled in an undergraduate course in the health area is considered a risk factor for BS development [10]. After the academic training period, the levels of stress, anxiety, and BS in newly formed dentists remain high and can be perpetuated throughout their professional life [20].…”
Section: Discussionmentioning
confidence: 99%
“…Many of them have somatic diseases (Maslak et al, 2014;Bessonova, Shkatova, & Oksuzyan, 2016). Another consequence of stress is burnout (Mazharenko, 2012;Maslak et al, 2014;Vered, Zaken, Ovadia-Gonen, Mann, & Zini, 2014;Kulkarni et al, 2016). The most significant factors in the burnout experienced by dentists are younger age, male sex, high job strain, excessive working hours and certain personality characteristics (Singh, Aulak, Mangat, & Aulak, 2016).…”
mentioning
confidence: 99%
“…Some dentists tend to be more susceptible to anxiety and depression (Kulkarni, Dagli, Duraiswamy, Desai, Vyas, & Baroudi, 2016). Many of them have somatic diseases (Maslak et al, 2014;Bessonova, Shkatova, & Oksuzyan, 2016).…”
mentioning
confidence: 99%